Development of Blended Learning Tools for Biodiversity Material to Increase Self Regulated Learning for Student - Arlynda Widya Apsari; Reni Ambarwati (Jurnal Inovasi Pembelajaran Biologi, 2023)
The six indicators of the Pancasila learner profile are noble character, independence, critical reasoning, creativity, mutual cooperation, and global diversity. The independent indicator is one that can be trained in biology learning. The benefit of being independent in learning was that students could understand their weaknesses and strengths. In the Merdeka Curriculum, class X is required to study biodiversity. An appropriate method is needed so that learning outcomes are achieved. One method that can be used to increase students' self-regulated learning is to implement blended learning using Canvas as a learning management system. This study aimed to produce learning tools in the form of the flow of learning objectives, teaching modules, and LKPD and describe the validity, practicality, and effectiveness of blended learning tools for biodiversity material to increase students' self-regulated learning. The research method used is research and development. The development stage was carried out at the UNESA Biology Department and then tested on a limited basis at Hang Tuah 2 Sidoarjo High School. Validity was measured based on the validator's assessment, practicality based on teacher and student responses to learning activities, and effectiveness based on student responses, and observations of self-regulated learning. The validation results show that the learning device is very valid with an average score of 4. Based on the teacher's response, the learning device received a response of 99% in the very good category, and then learning based on student responses was 98.6%. The self-regulated learning of students after participating in learning was 93% in the very high category. So that learning devices are proven to be valid, practical, and effective for use in blended learning.